Is Hardware Removal Recommended after Ankle Fracture Repair?. (13th October 2016) - Jung, Hong-Geun; Kim, Jin-Il; Park, Jae-Yong; Park, Jong-Tae; Eom, Joon-Sang; Lee, Dong-Oh
Abstract : The indications and clinical necessity for routine hardware removal after treating ankle or distal tibia fracture with open reduction and internal fixation are disputed even when hardware-related pain is insignificant. Thus, we determined the clinical effects of routine hardware removal irrespective of the degree of hardware-related pain, especially in the perspective of patients' daily activities. This study was conducted on 80 consecutive cases (78 patients) treated by surgery and hardware removal after bony union. There were 56 ankle and 24 distal tibia fractures. The hardware-related pain, ankle joint stiffness, discomfort on ambulation, and patient satisfaction were evaluated before and at least 6 months after hardware removal. Pain score before hardware removal was 3.4 (range 0 to 6) and decreased to 1.3 (range 0 to 6) after removal. 58 (72.5%) patients experienced improved ankle stiffness and 65 (81.3%) less discomfort while walking on uneven ground and 63 (80.8%) patients were satisfied with hardware removal. These results suggest that routine hardware removal after ankle or distal tibia fracture could ameliorate hardware-related pain and improves daily activities and patient satisfaction even when the hardware-related pain is minimal.